2014
DOI: 10.1111/cdev.12305
|View full text |Cite
|
Sign up to set email alerts
|

Why Does Infant Stepping Disappear and Can It Be Stimulated by Optic Flow?

Abstract: Two independent experiments (n = 22 and n = 22) showed that 2-month-old infants displayed significantly more stepping movements when supported upright in the air than when supported with their feet contacting a surface. Air- and surface-stepping kinematics were quite similar (Experiment 2). In addition, when data were collapsed across both experiments, more air steps and more donkey kicks were seen when infants were exposed to optic flows that specified backward compared to forward translation. The findings ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 43 publications
5
14
0
Order By: Relevance
“…Curiously, the amount of air stepping in the approaching optic flow condition was the lowest in the three air stepping conditions, just the opposite of what was observed in newborns (Barbu-Roth et al, 2009, 2013), and seemingly inconsistent with recent reports of enhanced tactile stepping frequency and quality in infants as young as two months of age (with and without disabilities) when optic flow is added to the treadmill on which they are stepping (Pantall, Teulier, Smith, Moerchen, & Ulrich, 2011; Pantall, Teulier, & Ulrich, 2012; Teulier, Barbu-Roth, & Anderson, 2014). Barbu-Roth et al (2015) did not have a tenable explanation for the effects of optic flow they observed in their two month-olds.…”
Section: Introductionmentioning
confidence: 76%
See 4 more Smart Citations
“…Curiously, the amount of air stepping in the approaching optic flow condition was the lowest in the three air stepping conditions, just the opposite of what was observed in newborns (Barbu-Roth et al, 2009, 2013), and seemingly inconsistent with recent reports of enhanced tactile stepping frequency and quality in infants as young as two months of age (with and without disabilities) when optic flow is added to the treadmill on which they are stepping (Pantall, Teulier, Smith, Moerchen, & Ulrich, 2011; Pantall, Teulier, & Ulrich, 2012; Teulier, Barbu-Roth, & Anderson, 2014). Barbu-Roth et al (2015) did not have a tenable explanation for the effects of optic flow they observed in their two month-olds.…”
Section: Introductionmentioning
confidence: 76%
“…Despite the convincing nature of the evidence provided by Thelen and colleagues to support the heavy legs hypothesis, recent findings reported by Barbu-Roth et al (2015) suggest the hypothesis may need modification. Barbu-Roth et al found that two month-old infants stepped significantly more when held upright in the air than when supported upright on a rigid surface.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations